Pencegahan Kanker Payudara melalui Edukasi Kesehatan SADARI pada Siswi Madrasah Aliyah Qamarul Huda - Lia Arian Apriani; Mustika Ayu Lestari; Ismiati Ismiati; Reza Indra Wiguna (Jurnal Abdimas Kesehatan (JAK), 2023)
Breast cancer is the highest cause of death for women in Indonesia. The number of deaths from breast cancer reached more than 22 thousand cases or 16.6% of 68,858 cases. The high incidence of breast cancer in women is caused by the lack of early health education. Therefore, this community service aims to increase student's knowledge about the early detection of breast cancer through BSE health education as a promotive and preventive effort. The target of this community service is 29 students at Islamic Senior High School Qamarul Huda. Health education media is used in the form of leaflets. This community service is an innovative health education that ends with a discussion and question and answer process for the students. Based on the results of the evaluation, it was found that the knowledge of students increased after BSE health education with an average knowledge level of 70.90 to 86.76 which means that the level of knowledge of students became good. This has a positive impact on aspects of knowledge and attitudes of students in carrying out early detection of breast cancer. Therefore, this community service is beneficial for students at Islamic Senior High School Qamarul Huda